Analysis average waiting time search performance in the queue process on CPU scheduling using the Round Robin, shortest job first and first in first out algorithm - Sonata, Fifin; Hutagalung, Juniar; Rachmad, Aeri (AIP conference proceedings, 2023)
In its activities, the CPU has a pattern of processes that coincide or precede each other. Where when one activity enters, another activity will come, and so on which is multiprogramming. Round Robin (RR), Shortest Job First (SJF), and First In First Out (FIFO) methods are CPU scheduling algorithms that are popularly used in multiprogramming systems. These three algorithms are used to find Average Waiting Time (AWT) with different process sequences. In the Round Robin algorithm, there is Qu that affects the number of process sequences. The AWT value is obtained from the number of waiting for processes divided by the number of existing processes. The makespan value in each algorithm must be the same even though the process sequence is different depending on the arrival time. This study describes and analyzes how the RR, SJF, and FIFO algorithms work in the queuing process on the CPU (Central Processing Unit). The result of this research is an analysis that is easy to understand in the form of an interactive programming application. In the resulting application, it can be seen that the queuing process in AWT runs in stages according to the principles of the three algorithms.